Field strength for graded Yang–Mills theory - Ilyenko, K. (Вопросы атомной науки и техники, 2001)
The graded field strength is defined for osp(2/1;C) non-degenerate gauge algebra. We show that a pair of Grassman odd scalar fields find their place as a constituent part of the graded gauge potential on the equal footing with an ordinary (Grassman even) one-form taking values in the proper Lie subalgebra, su(2), of the graded Lie algebra. Some possibilities of constructing a meaningful variational principle are discussed.